Study on Inversion of Mining Subsidence Based on PSO-BP Algorithm for Okada Model - Jifeng, Wu; Zhiqiang, Yang; Xiaolong, Wu (The open petroleum engineering journal, 2015)
This paper makes a systematic research of the Okada dislocation theory. The application of the theory in the mining subsidence is analyzed. And the method of inversion based on the PSO-BP algorithm has been presented. Through searching for the simulating value of the objective function and comparing with the field observation, the mining subsidence mechanism and movement law was studied in depth.